1995
DOI: 10.1146/annurev.pu.16.050195.001121
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Health in the Construction Industry

Abstract: Workers in the building. renovation, and demolition of roads and commercial structures in the U.S. suffer a disproportionate share of occupational fatalities and lost-time injuries. Nearly all of the injuries and deaths are preventable.The fatality rate from work-related ailments. such as cancers and silicosis, is believed to be excessive, but is not generally computed. The safety and health problems are tied largely to the construction industry'S organization and how the work is performed. Many hazardous expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(81 citation statements)
references
References 8 publications
3
74
0
Order By: Relevance
“…Carpenters working for larger contractors also reported greater frequency of safety training, greater availability of personal fall arrest equipment, and greater familiarity with the contractors' fall protection. Our findings of greater safety compliance and training in large contractors appear to be in concert with Ringen et al [1995], who found higher rates of injuries among smaller sized contractors. It is likely that larger contractors have more safety professionals or financial resources to provide safety training, equipment, monitoring, and enforcement.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Carpenters working for larger contractors also reported greater frequency of safety training, greater availability of personal fall arrest equipment, and greater familiarity with the contractors' fall protection. Our findings of greater safety compliance and training in large contractors appear to be in concert with Ringen et al [1995], who found higher rates of injuries among smaller sized contractors. It is likely that larger contractors have more safety professionals or financial resources to provide safety training, equipment, monitoring, and enforcement.…”
Section: Discussionsupporting
confidence: 74%
“…Workers with less experience [Salminen, 1994], including those with shorter periods of union membership [Stern et al, 1995], those employed by smaller size contracting companies [Ringen et al, 1995], and those who perform residential construction [Lipscomb et al, 2003] are more likely to experience occupational injuries. According to the Bureau of Labor Statistics [2008], in the 3-year period between 2003 and 2006, carpenter deaths due to falls to a lower level rose 40% in the United States.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because studies have shown that safety standards have environmental implications and project delivery consequences and vice versa ). Ringen et al (1995) has also reported that the aim of ensuring health and safety practice in project delivery is to reduce the number of accidents and accidents" effects on project costs such as the cost of insurance, inspection and conformance to regulations.…”
Section: Component 5: Business and Ethical Managementmentioning
confidence: 99%
“…However, nearly all injuries and illnesses occurring in the field of construction industry seem to be preventable because the safety and health problems are closely related to the organisation of building projects and performance of manual tasks [11]. Most risks in the construction industry may result from an insufficient communication of site information and inadequate measurement technologies [11].…”
Section: Introductionmentioning
confidence: 99%